2021
DOI: 10.1111/mpp.13172
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between abiotic (drought) and biotic (virus) stresses in tomato plants

Abstract: Environmental stresses affect agricultural production worldwide, leading to yield reductions of many crops. Drought and heat are the most serious abiotic stresses, especially in countries with hot climates. Drought, together with heat, usually stimulates plant pathogens such as viruses, bacteria, fungi, and insects. Interactions between the plant environment and pathogens modulate the plant defence responses (Prasch & Sonnewald, 2013), either weakening or enhancing them (Atkinson & Urwin, 2012).An increasing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…The ability of TYLCV, particularly of its C4 protein, to promote enhanced tolerance to drought was reported in tomato and in N. benthamiana ; however, a mechanism explaining this phenomenon was not proposed [ 13 ]. Indeed, TYLCV-infected tomatoes survived after 25–30 days of growth after water withhold, compared to approximately two weeks for uninfected tomatoes [ 39 ]. The observed resilience of virus-infected plants to drought was accompanied by a reallocation of key metabolites, from shoots to roots ( Figure 3 ).…”
Section: Tylcv Infection Of Tomatoes Enhances Tolerance To Droughtmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of TYLCV, particularly of its C4 protein, to promote enhanced tolerance to drought was reported in tomato and in N. benthamiana ; however, a mechanism explaining this phenomenon was not proposed [ 13 ]. Indeed, TYLCV-infected tomatoes survived after 25–30 days of growth after water withhold, compared to approximately two weeks for uninfected tomatoes [ 39 ]. The observed resilience of virus-infected plants to drought was accompanied by a reallocation of key metabolites, from shoots to roots ( Figure 3 ).…”
Section: Tylcv Infection Of Tomatoes Enhances Tolerance To Droughtmentioning
confidence: 99%
“…Drought causes a decrease in essential free sugars and amino acids in shoots, concomitant to an increase in these metabolites in roots [ 40 ]. The reallocation of carbohydrates and amino acids from shoots to roots suggests a role of roots in protecting infected tomatoes against drought [ 39 ].…”
Section: Tylcv Infection Of Tomatoes Enhances Tolerance To Droughtmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in transmission frequency of ASbLV to different seedling tissues in the case of the one infected paternal parent crossing ('X84', Table 1) where this was investigated (deviance = 0.1, 2 df, P = 0.967). they can confer tolerance to drought or freezing temperatures in several different crops (Roossinck 2011;Mishra et al 2022). Specific research is required to understand the ASbLV-Actinidia interaction including ASbLV movement and whether it confers benefit under a range of biotic and abiotic conditions.…”
Section: Transmission From Infected Pistillate (Female) Parentsmentioning
confidence: 99%
“…In the context of drought-induced responses, transcriptome analyses showed that TYLCSV infection boosts the expression of ABA biosynthetic genes, supporting the increase in ABA levels in virus-infected tissues [ 31 ]. More recently, Tomato yellow leaf curl virus (TYLCV), a relative of TYLCSV, was reported to mitigate the response of tomato plants to heat stress [ 32 ] and to increase drought tolerance in Nicotiana benthamiana and tomato [ 33 35 ]. The study by [ 33 ] also advanced that the TYLCV-encoded C4 protein is the viral determinant conferring such features in Arabidopsis , in an ABA-independent manner.…”
Section: Introductionmentioning
confidence: 99%